A Jungian Interpretation of The Hunger Games: A Myth that Defines Our Times. (3rd July 2018) - Merritt, Frazer; Merritt, Dennis; Lu, Kevin
ABSTRACT: C. G. Jung's literary theories provide insights into the archetypal dynamics behind Suzanne Collins's The Hunger Games and help elucidate the trilogy's astonishing global popularity. President Snow represents a senex archetype whose reign has petrified and is in need of renewal, whereas Katniss represents a feminine hero aligned with the Self. Jung believed myths compensate for the one-sided dominant attitude of an era, and it is plausible The Hunger Games speaks to the present-day danger of an overly powerful senex in the form of big government and corporate power. Published in 2008, the story offers a metaphoric understanding of the deep dissatisfaction with the Bush administration.